Pré-aposentadoria docente em instituição de ensino superior pública: pesquisa de métodos mistos - Bordignon, Isabel Cristine Oliveira (2024)
Population aging is a global phenomenon, triggered especially by the rapid increase in life expectancy. As a result of greater longevity, it appears that many workers are in the process of retiring. This phase is accompanied by many transformations, which can trigger positive or negative effects. Specifically, the pre-retirement experienced by federal teachers needs to be evaluated and contextualized through the subjectivities and singularities of the worker inserted in the teaching work environment. The main objective of this study is to analyze the preparation for retirement of teachers in a public Higher Education Institution in Rio Grande do Sul. Mixed methods study, with a sequential explanatory approach in two phases (QUANT - qual). The setting was a public university in Rio Grande do Sul. The population was made up of 89 professors who voluntarily were willing to take part in the research. The first phase of a quantitative approach took place via an online questionnaire system, with a descriptive crosssectional design using three self-administered instruments: a sociodemographic, occupational and health questionnaire; the Retirement Planning Behavior Change Scale and the Retirement Planning Process Scale. Data were analyzed using descriptive and inferential statistics. The second phase, with a qualitative approach, took place based on the results of the previous stage, based on an exploratory-descriptive design, through individual semi-structured interviews. The data were subjected to thematic analysis with the help of MaxQDA software. The results were connected, revealing a comprehensive understanding of the topic investigated. Phase I consisted of 89 participants, 51% male and 49% female, aged between 54 and 75 years. Phase II was comprised of 11 teachers, the majority of whom were female (98%), with ages ranging from 59 to 65 years old. The prevalent retirement planning behavior change stage was Action (43%), with the main investment in financial planning (18%). There was no identification of the precontemplation and contemplation stages. The domain related to investment in Autonomy and Well-Being behaviors had a higher average when compared to investment in Occupational – Social behaviors (p<0.001). In the Retirement Planning Process Scale, the mean dimensions were similar, mainly between health and financial planning (3.40±SD) and between lifestyle and psychosocial (3.02±SD). Lifestyle planning had the lowest evaluation among the four dimensions and financial planning was the best evaluated. It was evident that health is a constant concern for teachers, thus, it is concluded that the data on the approaches used complement each other, noting that periodic health consultations and exams, healthy eating, regular physical activities, in addition to time on the agenda to cultivate friendships and family coexistence are the main actions taken by teachers. This study is expected to obtain subsidies that make it possible to assist in assistance practices in the health-disease process, work and management of educational institutions, with regard to teachers in the process of retirement and/or the entire teaching universe with lifelong learning (lifelong education).